2013
DOI: 10.1002/cpdd.47
|View full text |Cite
|
Sign up to set email alerts
|

GCG100649, A Novel Cyclooxygenase‐2 Inhibitor, Exhibits a Drug Disposition Profile in Healthy Volunteers Compatible With High Affinity to Carbonic Anhydrase‐I/II: Preliminary Dose–Exposure Relationships to Define Clinical Development Strategies

Abstract: CG100649, proposed as a dual inhibitor of cyclooxygenase (COX)-2 and carbonic anhydrase (CA)-I/-II, is long-lived in plasma and whole blood. The mean ± SD half-lives were 131 ± 19 and 127 ± 33 hours, respectively, after administration of oral single doses of 2 or 8 mg CG100649 to healthy volunteers. The whole blood to plasma concentration ratio (78 ± 23) for CG100649 is linear over the dosing interval reflecting a biodistribution pattern consistent with other strong CA-inhibitors (e.g., acetazolamide, methazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Polmacoxib, also known as (CG-100649), is a first-in-class NSAID which is a dual inhibitor of COX-2 and carbonic anhydrase (CA) . The drug, which was approved in South Korea for the treatment of colorectal cancer (CRC) in 2015 and whose discovery has been described by workers at AmorePacific R&D, interacts with CA in red blood cells, providing a novel “tissue-specific” transport mechanism that is designed to deliver sustained levels of drug to inflamed tissues while maintaining low systemic exposure .…”
Section: Musculoskeletal Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polmacoxib, also known as (CG-100649), is a first-in-class NSAID which is a dual inhibitor of COX-2 and carbonic anhydrase (CA) . The drug, which was approved in South Korea for the treatment of colorectal cancer (CRC) in 2015 and whose discovery has been described by workers at AmorePacific R&D, interacts with CA in red blood cells, providing a novel “tissue-specific” transport mechanism that is designed to deliver sustained levels of drug to inflamed tissues while maintaining low systemic exposure .…”
Section: Musculoskeletal Drugsmentioning
confidence: 99%
“…Polmacoxib, also known as (CG-100649), is a first-in-class NSAID which is a dual inhibitor of COX-2 and carbonic anhydrase (CA). 113 The drug, which was approved in South Korea for the treatment of colorectal cancer (CRC) in 2015 and whose discovery has been described by workers at AmorePacific R&D, 114 interacts with CA in red blood cells, providing a novel "tissue-specific" transport mechanism that is designed to deliver sustained levels of drug to inflamed tissues while maintaining low systemic exposure. 115 Although the unique dual COX-2/CA inhibition is designed to provide potentially superior safety to cardiovascular, renal, and gastrointestinal tissues compared to traditional NSAIDs or COX-2 inhibitor drugs, the long-term safety profile of the drug, particularly cardiovascular risks notoriously associated with inhibition of COX-2, 116 has yet to be determined, and the drug is currently not approved for use in any other country outside of South Korea.…”
Section: Metabolic Drugsmentioning
confidence: 99%
“…The area under the plasma concentration-time curve (AUC) following a 2 mg single dose of polmacoxib was 632.9 (162.1) ng/mL × h, whereas the AUC following an 8 mg single dose of polmacoxib was 2,366.8 (761.9) ng/mL × h [14]. The mean elimination half-lives following single oral doses of polmacoxib 2 and 8 mg were found to be 131 (19) and 127 (33) hours, respectively [15].…”
Section: Pharmacokinetics Of Polmacoxibmentioning
confidence: 97%
“…Thirdly, polmacoxib 2mg was considered "acceptable" for the safety profile and over a trial period of 6 months, polmacoxib was noticed to be well-tolerated and showed higher efficacy than placebo and was same as celecoxib in this profile. Lastly, the trial was concluded with the statement that polmacoxib 2mg showed possibility for a pain relief treatment usage with lessened gastrointestinal adverse effects in comparison to the other NSAID class of drugs 19,20 . Patent information of polmacoxib drug describes the preparation of polmacoxib using solvents like dimethyl sulfoxide and methanol along with purified water and hydroxylamine-O-sulfonic acid.…”
Section: Drugmentioning
confidence: 99%